"Ballistic" waves among chemically oscillating micromotors. Issue 68 (5th August 2021) - Wang, Qizhang; Zhou, Chao; Huang, Luyang; Wang, Wei
Abstract : Motion waves propagating in one direction emerge from a population of chemically oscillating micromotors. Active motors on the wavefront move in random directions leading to a "ballistic" type wave. Abstract : Coordinating a group of chemically powered micromotors holds great importance in potential applications that involve a large population in a complex environment, yet information transmission at a population scale remains challenging. To this end, we demonstrate how propagating waves emerge among a population of spontaneously oscillating micromotors that dash toward a direction prescribed by their Janus orientations (termed a "ballistic" wave). Moreover, chemical communication among these micromotors enables the tuning of the speed and frequency of individual micromotors and their waves, by varying the population density or the viscosity of the medium.